Air Pollution Meteorology - Pérez, Isidro A.; García, M. Ángeles (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Although air pollution is usually linked with human activities, natural processes may also lead to major concentrations of hazardous substances in the low atmosphere. Pollutant levels may be reduced when emissions can be controlled. However, the impact of meteorological variables on the concentrations measured may be noticeable, and these variables cannot be controlled. This book is devoted to the influence of meteorological processes on the pollutant concentrations recorded in the low atmosphere. Measurements, cycles, statistical procedures, as well as specific variables such as the synoptic pattern, temperature inversion, or the calculation of back-trajectories, are considered in the studies included in this book to highlight the relationship between air pollution and meteorological variables. In addition, the state of the art of this subject following meteorological scales, from micro to macro-scale, is presented. Consequently, this book focuses on applied science and seeks to further current knowledge of what contribution meteorological processes make to the concentrations measured in order to achieve greater control over air pollution.